2016
DOI: 10.18311/ajprhc/2016/4595
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Adequacy Index in Young People in Syria

Abstract: Objective: To assess, the degree of adherence to Mediterranean Diet (MD) in Syrian young people, and studying the effect of some variables on Mediterranean Adequacy Index (MAI) value and its comparison with other studies in Spain and Mediterranean area. Background: It has been observed that the Syrian population, especially the young ones, are abandoning the (MD), which affects in long term their health, the same has been observed in Spanish youth. The longitudinal study of the "seven counties" involved active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…Additionally, chicken was preferred by more than half of the participants over meat, primarily among the Syrian population This result is similar to other studies showing that Syrian populations are having a higher tendency toward protein intake, which is mainly chicken ( 26 ). Consumption of sofrito was also quite common among participants Cooking using sofrito is very usual among Mediterranean people as it is a typical Mediterranean sauce, strongly associated with a reduced risk of CVD ( 46 ).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Additionally, chicken was preferred by more than half of the participants over meat, primarily among the Syrian population This result is similar to other studies showing that Syrian populations are having a higher tendency toward protein intake, which is mainly chicken ( 26 ). Consumption of sofrito was also quite common among participants Cooking using sofrito is very usual among Mediterranean people as it is a typical Mediterranean sauce, strongly associated with a reduced risk of CVD ( 46 ).…”
Section: Discussionsupporting
confidence: 88%
“…Differences in adherence were also seen among genders, where men had higher adherence than women This result is complementary to other studies, where females showed a lower adherence than males, among under 30-year-old Lebanese adults ( 35 ) and young Syrian people ( 26 ). This difference can be explained by the focus of women on body image, which leads to reducing calorie intake and healthy eating ( 36 ).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations